ANALYSES OF THE WAYS TO ACCESS MOKHADHAMMA IN THE THERAVADA BUDDHISM - Mrs. Navarat Aungsupanith (Journal of Contemporary Buddhist Society = JCBS, 2023)
Analyses of the Ways to Access Mokhadhamma in the Theravada Buddhism was aimed to analyze the ways to access Mokhadhamma in the Theravada Buddhism; to investigate ways of practices to eliminate Kilesa (defilements) founded on the Buddhist principles and to propose the approaches to liberation by ability and perseverance of each individual. The researcher found that in the concept of the way of attaining Mokhadhamma or Bodhipakkhiyaya in the Theravada Buddhism, it included the 4 Satipatthana (foundations of mindfulness); the 4 Sammappadhana (exertion/efforts); Iddhipãda (path of accomplishment/to success); 5 Bala (power); the 7 Bojjhanga (enlightenment factors); and the 8 Magga (the Noble Eightfold Path). The approaches to eliminate defilements founded on the Buddhist principles engaged the 3 Puññakariyã-vatthu (bases of meritorious action); Samathakammatthana (concentration development); and Vipassanãkammatthana (insight development). The researcher recommended that observation of the 5 precepts and meritorious action consisting in mental development should be written in the organizational policy and in practice since they owned low cost. As of further studies, the 4 Sangahavatthu (social solidarity) should be investigated whether it would lead Laities to Nibbana and for religious persons, the principles in deep of Vipassanãkammatthana should be investigated so that the novices and the religious women would gradually practice Dhamma from easiness to rigid routes for their peace of their mind to step into Nibbana.